2020
DOI: 10.1038/s41586-020-2470-y
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism links astroglial mitochondria to cannabinoid effects

Abstract: S and A.A. performed and supervised in vitro experiments in cell/astrocyte cultures and ex vivo analysis of brain tissue; A.B.G, C.I. and P.G.S. performed behavioral experiments and surgical procedures in mice; E.R. and M.G. provided some CB1-KO mice to the group of J.P.B.; D.A and A.P. performed electrophysiological experiments not shown in the manuscript; M.V. and F.J.K performed mouse perfusion and immunohistochemistry experiments; A.C. and L.B. produced some of the viral constructs used (e.g. Syn-mitoCAT);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
203
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(218 citation statements)
references
References 53 publications
(95 reference statements)
8
203
0
1
Order By: Relevance
“…Although those findings came with their share of controversies [81,82], there is now a well-established link between cannabinoids, mitochondria and neuronal activity [83][84][85]. However, Jimenez-Blasco et al describe in a recent study how the activation of mitochondrial CB1 actually reduces OXPHOS and hampers the metabolism of glucose in mouse astroglia [86]. In this study, they first confirmed that mitochondrial CB1 was responsible for reducing microglia oxygen consumption by comparing the effect of HU210, a CB1 agonist, with that of a cell-impermeable biotinylated version.…”
Section: Cannabinoids Mitochondria and The Nervous Systemmentioning
confidence: 99%
“…Although those findings came with their share of controversies [81,82], there is now a well-established link between cannabinoids, mitochondria and neuronal activity [83][84][85]. However, Jimenez-Blasco et al describe in a recent study how the activation of mitochondrial CB1 actually reduces OXPHOS and hampers the metabolism of glucose in mouse astroglia [86]. In this study, they first confirmed that mitochondrial CB1 was responsible for reducing microglia oxygen consumption by comparing the effect of HU210, a CB1 agonist, with that of a cell-impermeable biotinylated version.…”
Section: Cannabinoids Mitochondria and The Nervous Systemmentioning
confidence: 99%
“…Furthermore, one study suggests that neuronal stimulation, at least in the hippocampus, triggers neuronal glycolysis and the release of lactate from neurons ( Diaz-Garcia et al, 2017 ). In contrast, many others provide evidence that lactate is released from astrocytes and delivered to neurons, both in response to cortical activation by arousal triggers ( Zuend et al, 2020 ) or stimulation with cannabinoids ( Jimenez-Blasco et al, 2020 ). As with most complicated systems in neuroscience, it is likely that all of these processes can occur depending on the exact stimulus, environment, and cells involved.…”
Section: Controversies Related To Lactate and Its Transporters In Thementioning
confidence: 99%
“…The different origins of cell types (rat versus humans) allowed us to investigate whether neuronal m.3243A>G heteroplasmy level, non-cell autonomously affected gene expression in astrocytes. This is important as astrocytes metabolically support neuronal ATP production by supplying lactate, via the "astrocyte-neuron lactate shuttle" (Araque et al, 1999;Genc et al, 2011;Jimenez-Blasco et al, 2020;Witcher et al, 2010). Gene expression profiles from astrocytes co-cultured with HH iNeurons (Astro+HH1 and Astro+HH2) were compared to astrocytes co-cultured with LH iNeurons (Astro+LH1 and Astro+LH2).…”
Section: Non-cell Autonomous Effects Of High M3243a>g Heteroplasmy Imentioning
confidence: 99%